The Relationship Between Marketing Mix And Consumer Buying Decision of Cactus at The Prickle House Salatiga During Covid-19 Pandemic - Riskawati, Sinta Nur; Yuliawati, Yuliawati - (JURNAL MANAJEMEN AGRIBISNIS; Vol 9 No 2 (2021): OKTOBER 2021DO - 10.24843/JMA.2021.v09.i02.p06, 2021)
Marketing mix is a marketing tool where companies use it continuously to achieve marketing objectives in the target market that is divided into 4P namely product, price, place, dan promotion. This study aims to determine the relationship of the marketing mix of internal factors, namely product, price, place and promotion with the consumer buying decision of cactus at The Prickle House Salatiga during the Covid-19 pandemic. The research location is chosen purposively. The types of data used are primary data and secondary data. The type of research used is explanatory research. The sampling was done deliberately to 50 respondents with the criteria of consumers who purchased cactus products during the Covid-19 pandemic since March 2020, posted them on their social media, tagged and reposted by The Prickle House Salatiga. The indicator of the research questionnaire was measured on the Likert scale. The research data will be analyzed statistically with Spearman Rank correlation test. The results showed that the Price, Location, and Promotion variables were significantly correlated with consumer buying decisions. Meanwhile, the product variable is not significantly correlated with the consumer buying decisions.